2022
DOI: 10.1136/bmjopen-2022-060973
|View full text |Cite
|
Sign up to set email alerts
|

What are the solutions for well-being and burn-out for healthcare professionals? An umbrella realist review of learnings of individual-focused interventions for critical care

Abstract: ObjectiveTo determine what, how, for whom and under what conditions individual-focused interventions are effective to improve well-being and decrease burn-out among critical care healthcare professionals.DesignThis study is an umbrella review that used the realist approach, using Realist and Meta-narrative Evidence Synthesis: Evolving Standards guidelines. PsycINFO, Web of Science, CINAHL, MEDLINE, Scopus, ClinicalTrials.gov and ISRCTN databases were searched for published and unpublished systematic reviews an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 86 publications
0
18
0
Order By: Relevance
“…This study identified theory prepositions that were previously reported in the umbrella review ( Adnan et al, 2022 ). This included (1) the use of a tailored intervention, (2) the process of learning and education, (3) engagement, and (4) maintaining the quality of interventions in terms of delivery, duration, and intensity.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…This study identified theory prepositions that were previously reported in the umbrella review ( Adnan et al, 2022 ). This included (1) the use of a tailored intervention, (2) the process of learning and education, (3) engagement, and (4) maintaining the quality of interventions in terms of delivery, duration, and intensity.…”
Section: Resultsmentioning
confidence: 95%
“…Twenty-one experts were interviewed to determine what individual interventions work for the critical care workforce, under what circumstances, and why. The program theory from an umbrella review was used to guide the questions and develop a refined program theory exclusively directed to critical care healthcare professionals ( Adnan et al, 2022 ). A wide range of experts from differing professional fields was included within the population sample, encompassing in gender, state/country, and specialty (academic/clinical) variations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations